White Supremacist Activity and Crossburnings in North Carolina - Green, Donald P. (Journal of quantitative criminology, 1998)
This study examines whether the incidence of crossburnings rises in areas where white supremacist organizations, such as the Christian Knights of the Ku Klux Klan, have held rallies or demonstrations. Using data from two public interest groups, Klanwatch and North Carolinians Against Racial and Religious Violence, we track crossburnings and white supremacist activities in 100 North Carolina counties annually for the period 1987–1993. Various statistical models, including an event count analysis that allows each county to have its own level or reporting bias, indicate that the base rate at which crossburnings occur rises sharply in counties where a demonstration has taken place. Since none of the suspected crossburners has apparent ties to white supremacist groups, it may be that white supremacist rallies encourage fellow travelers to engage in this form of racial intimidation.